An innovative method used for the identification of N-glycans on soybean allergen β-conglycinin - Cheng Li; Yang Tian; Jianli Han; Yu Lu; Meiyi Zou; Yue Jia; Chengjian Wang; Linjuan Huang; Zhongfu Wang (Food Science and Human Wellness)
β-Conglycinin is one of the major allergens existed in soybean. N-Glycans attached to the β-conglycinin influenced the immunoreactivity and antigen presenting efficiency of β-conglycinin. In this study, we described a new method used to release and collect the N-glycans from β-conglycinin, and the N-glycans existed in linear epitopes of β-conglycinin were identified. Glycopeptides hydrolyzed from β-conglycinin were purified by cotton hydrophilic chromatography. Trifluoromethylsulfonic acid was then used to release glycans from glycopeptides, and new glycopeptides containing one single N-acetyl-D-glucosamine (GlcNAc) moiety were then utilized for mass spectrometry. Five glycosylation sites (Asn-199, Asn-455, Asn-215, Asn-489 and Asn-326) and 22 kinds of glycopeptides were identified. It is noteworthy that the peptide VVN#ATSNL (where # represents for the glycosylation site) was analyzed to be both glycopeptide and linear epitope. Our results provided a new method for the N-glycoform analysis of food allergens, and laid a foundation for understanding the relationship between glycosylation and food allergy.